Monitoring vpliva rastlinojedov na naravno obnovo gozdov - Perko, Franc (Gozdarski vestnik, 2009)
This article evaluates the monitoring of the influence of the herbivorous game on the natural forest regeneration, performed by Slovenia Forest Service. The monitoring is analyzed with regard to the data from the Long-term Plans for Hunting Management Areas for the Period 2007-2016.
Keywords: lovstvo; načrtovanje; obnova gozda; divjad; Slovenia; Slovenija